Peran Home Industry Ocean Frozen dalam Meningkatkan Kesejahteraan Karyawan: Kajian Maqashid Syariah dalam Perspektif Ekonomi Islam - Bedyawan, Hanita Seva (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: Home industry refers to activities that are managed by maximizing skills to create value in goods or services produced through production activities. Home industries do not require extensive land or large production spaces. However, Ocean Frozen is a home-based culinary business with adequate space and equipment. Ocean Frozen is classified as a small business because production activities are carried out at home. This research aims to explain the role of the Ocean Frozen home industry in improving employee welfare from the perspective of Islamic economics in Dawung Village, Ringinrejo District, Kediri Regency. Research Methods: This study employs a descriptive qualitative method. Data collection techniques used in this research include observation and interviews. The informants in this study are the owner of Ocean Frozen and seven permanent employees. Results: The findings indicate that the Ocean Frozen home industry plays a significant role in creating job opportunities for local residents in need of employment and enhancing the welfare of its employees. Employee welfare at Ocean Frozen can be measured through indicators of welfare in Islamic economics. Conclusion: In conclusion, the Ocean Frozen home industry serves as a vital contributor to the economic welfare of its employees, aligning with the principles of Islamic economics. By creating job opportunities and enhancing the quality of life for local residents, Ocean Frozen exemplifies the potential of home industries in promoting sustainable economic development.